Carcinosarcoma of lung - Neupane, S; Pathak, T; Bastola, S; Shrestha, S; Pun, CB (Journal of Pathology of Nepal, 2013)
Primary carcinosarcoma of the lung is exceedingly rare. It is described as malignancy composed of a mixture of carcinoma and sarcoma elements. The sarcomatous element is usually spindle cell but may contain cartilage, bone or skeletal muscle. We report a case of pulmonary carcinosarcoma in a 66 years male who presented with cough, chest pain on exertion, anorexia and weight loss. Brush cytology revealed poorly differentiated non-small cell carcinoma. Histopathological examination showed proliferation of malignant spindle cells containing bone and malignant cartilage admixed with areas of keratinized squamous cells with few foci of ill-defined glandular structure. On immunohistochemistry, carcinomatous component of tumor showed positivity for cytokeratin AE1/AE3 and spindle cell component were positive for vimentin. These findings led to diagnosis of carcinosarcoma. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 419-421 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7873